EMA approved orphan medicines since the implementation of the orphan legislation - Eveliina Hahl; Terhi Kurko; Hanna Koskinen; Marja Airaksinen; Kati Sarnola (Orphanet Journal of Rare Diseases)
Abstract Background In the European Union (EU), the orphan legislation, aiming to increase the number of pharmacotherapies available for rare diseases, came into force in April 2000. This study examined the development of the selection of orphan medicines granted marketing authorisation, their approved indications, and the number of orphan medicines developed for paediatric use in EU during 2000–2022. This study also examined the availability of the orphan medicines with a marketing authorisation in the Finnish market in order to demonstrate their country level uptake in a single member state. Methods The material on orphan medicines’ marketing authorisations and their introduction were collected from the European Commission’s Community Registers in June 2022 and analysed with a qualitative document analysis. This study covered the period 2000–2022 since the introduction of the orphan legislation, and comparisons were made in 10-year periods of, 2001–2010 and 2011–2020. Results By May 2022, there were 213 novel orphan medicines approved in Europe during the observation period. Of them, 67% (n = 142) were on the market in Finland in May 2024. The number of new orphan medicines approved in Europe doubled from 63 products in 2001–2010 to 127 products in 2011–2020. Several orphan medicines were developed for certain type of rare diseases, such as haematological cancers. The proportion of orphan medicines approved for paediatric use decreased from 55% in 2001–2010 to 42% in 2011–2020. Conclusion The number of orphan medicines available within EU increased significantly after the orphan legislation came into force. The development of orphan medicines seemed to often focus on diseases or disease groups that already have available treatment options, while several rare diseases remain without available treatment. Even though rare diseases are more common in children, orphan medicines have not been developed for paediatric use in the same proportion.